Psychological resilience buffers the association between cell phone addiction and sleep quality among college students in Jiangsu Province, China - Xie, Guangming; Wu, Qi; Guo, Xiaohan; Zhang, Jinpeng; Yin, Dehui (Frontiers in Psychiatry, 2023)
Background and Aims: Excessive use of cell phones can take up college students' time and energy, and the sleep quality will inevitably be affected. A high level of psychological resilience can help them to maintain positive attitude and cope with stressful events. However, few studies were conducted to investigate the effects of psychological resilience buffering cell phone addiction on sleep quality. In our hypothesis, psychological toughness would mitigate the worsening impact of cell phone addiction on sleep quality. Methods: The sample consisted of 7,234 Chinese college students who completed an electronic questionnaire that included demographic characteristics, such as the Mobile Phone Addiction Index (MPAI), the Psychological Resilience Index (CD-RISC), and the Pittsburgh Sleep Quality Index (PSQI). SPSS 26.0 was used for data analysis, the measurement data were described by ±s for those conforming to normal distribution, and the comparison of means between groups was analyzed by group t-test or one-way ANOVA. Those that was not conforming to normal distribution were described by median M (P25, P75), and the comparison of M between groups was analyzed by Mann-Whitney U test and Kruskal-Wallis H test. Using Spearman correlation analysis, the associations between mobile phone addiction, psychological resilience, and sleep quality were evaluated. Using SPSS Process, the mediating role of psychological resilience was examined. Results: The mean scores of cell phone addiction and psychological resilience were 45.00 (SD=13.59) and 60.58 (SD=18.30) respectively; the sleep quality score M (P25, P75) was 5.0 (3.0, 7.0). Cell phone addiction among college students had a direct predictive effect on sleep quality (β=0.260, P<0.01), and psychological resilience had a negative correlation with both cell phone addiction and sleep quality (β=-0.073, P<0.01, and β= -0.210, P<0.01). Psychological resilience was responsible for a mediating effect value of 5.556% between cell phone addiction and sleep quality. Conclusion: Cell phone addiction has an impact on sleep quality both directly and indirectly through the mediating effect of psychological resilience. Increased psychological resilience has the potential effect to buffer the exacerbating of cell phone addiction on sleep quality. These findings provide evidence for cell phone addiction prevention, psychological management, and sleep improvement in China.